Status Trofik Perairan Universitas Riau Provinsi Riau Berdasarkan Trophic state index (TSI) - Irfan Anggriawan; Tengku Dahril; Asmika H Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractSeveral activities in the waters around the University of Riau provide input of organic and inorganic materials which have an impact on water quality including nutrient concentrations in the waters. This research has conducted from June to July 2020. The study aim to know  the trophic status of the waters around the Riau University campus based on the Trophic State Index (TSI).  Sampling was carried out on the surface (0.5 m) waters,once/week, durung 2 weeks.  Water quality parameters measured were transparency, total P, and chlorophyll -a, where as supporting water quality parameters such as temperature, pH, and dissolved oxygen (DO). The results shown transparency ranged 34 - 83.5 m, Total P ranged 0.301 - 0.599 mg / L, and chlorophyll-a ranged  0 , 56 - 5.03 µg / L. temperature ranges 30.3 - 31 0C, pH 6, and DO ranges  4.966 - 5.64 mg / L, and TSI value ranged  58,13 - 70,14.  Based on data obtained, it can be concluded that the trophic state of  waters around the Riau University can be category mild eutrophic to severe eutrophic. Keywords: Water quality, Carlson 'Trophic State Index, Mild Eutrophic to severe Eutrophic Riau University